1021 Characterization of Key Enzymes of the Steroid Biosynthesis in Preterm Infants. (October 2012) - Laffolie, J de; Kästner, L; Wudy, SA; Kampschulte, B; Grofer, B; Bödecker, RH; Heckmann, M
Abstract : Background: A suspected cause for relative adrenal insufficiency in preterm infants is the immaturity of adrenal key enzymes for steroid synthesis (3ß-hydroxysteroiddehydrogenase (3ß-HSD), 11ß-hydroxylase (11ß-HYD)). The fetus lacks 3ß-HSD activity until the last trimenon (requiring placental progesterone) and active cortisol concentration is regulated by the final step of synthesis 11ß-HYD and inactivation by 11ß-hydroxysteroiddehydrogenase type 2 (11ß-HSD2). In this study we estimate enzyme activity in preterm infants and compare steroid profiles of preterm infants < 30 weeks gestational age (GA) and above. Method: A 24 hour profile of glucocorticoid metabolites was obtained in the urine of 61 preterm infants of < 30 wks GA and 81 preterm infants > 30 wks GA using gaschromatography-massspectrometry (GC-MS). Results: Patients < 30 wks GA in contrast to the patients >30 wks displayed a significant increase in 3ß-HSD activity from day 3 to week 3. 11ß-HYD activity decreased significantly until third week of life, this trend was stronger in preterm infants < 30 weeks. In patients < 30 weeks GA, 11ß-HSD activity decreased postnataly until the third week of life to the level of more mature patients. Conclusion: Preterm infants < 30 weeks showed significant changes in enzyme activity, possibly a sign of maturation processes, that are not observed in patients > 30 weeks GA. There was no significant difference between ill and well preterm infants, potentially signifying insufficient cortisol response and validating further study in stress response at different stages of maturation.